Percepción de amenaza, ideología política y dinámicas intergrupales en la migración venezolana en Perú y Colombia - Lerner Puyó, Antonia (2025)
This research aimed to analyze the role of political ideology, appraisal, emotions, and intergroup stereotypes in the perception of threat concerning Venezuelan immigration in a Peruvian and a Colombian sample. To this end, 319 participants were surveyed, 132 Colombians and 187 Peruvians between the ages of 17 and 80. Significant differences were found according to nationality in emotions, stereotypes, intergroup appraisal, and perception of threat, with the Colombian sample showing a more negative affective and cognitive response to Venezuelan migration. In addition, differentiated effects are identified in both samples of cognitive and affective variables as predictors of real and symbolic threat, highlighting the role of authoritarianism, prejudice, and intergroup stereotypes in both cases.